PENGEMBANGAN BAHAN AJAR IPS BERBASIS KARAKTER DENGAN MEDIA KARTU PINTAR PADA MATERI TOKOH-TOKOH HINDU, BUDHA, DAN ISLAM DI INDONESIAPADA SISWA KELAS V SDN 01 SRIWIJAYA - Ahmad Wahyudi; Nanang Abdul Jamal (STAI Al-Ma`arif Way Kanan Lampung, 2021)
ABSTRACT This study aims to 1) develop the teaching materials of the character-based social science used smart card media, 2) know the quality of the content and the appearance of the teaching materials of the character-based social science used smart card media, 3) know the student assessment towards the teaching materials of the character-based social science used smart card media, 4) know the improvement of student achievement of the fifth grade in 01 Sriwijaya Elementary School through developing the teaching materials of the character-based social science used smart card media on changes on earth appearance and sky objects. This study was conducted in 01 Sriwijaya Elementary School. This was a Research and Development (R&D) with 23 students in total as samples. The development of smart card media in the study included 10 steps consisting of: 1) the potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6)product trial, 7)product revision, 8) utility testing, 9) revision of the product and 10) mass production. Interview, test, observation, questionnaire, and documentation were used to collect the data. The data analysis techniques used descriptive analysis. Based on the results of the study, it can be concluded that 1) the development on teaching materials of the character-based social science used smart card media was done trought systematic steps, 2) the quality of the content and the appearance of the teaching materials of the character-based social science used smart card media based on material expert validation obtained 3.33 score in average in the middle deverse category wheres from media expert assessment it reached 2.91 score in average in the middle deserve category, 3) Students evaluation towards the teaching materials of the character-based social science on limited testing gained 3.4 in average in deserve category and the evaluation result on field testing showed 3.5 score in average in the deserve category. 4) the teaching materials of the character-based social science used smart media card could improve the student achievement of the fifth grade in 01 Sriwijaya Elementary School which can be proved by the increase of the students average score and most of the students had not passed the passing grade. In the limited testing, the pre-test showed 5.5 score in average and most of the students had not passed the passing grade (66.7%), while the post-test showed 7.33 score in average and all students passed the passing grade (100%). In the field testing, the pre-test showed 6.35 score in average and most of the students had not passed the passing grade (52.9%), while the post-test showed 7.82 score in average and most students passed the passing grade (94.1%).